Workshop Peningkatan Keterampilan Motorik Anak Usia Dini dengan Menggunakan Permainan Sederhana di Desa Dalisodo - Rizki Aprilia Dwi Susanti; Moh. Askiyanto; Sri Indah; Muhammad Fauzy Emqi; Retno Ayu Dewi Novitawati (WIDA Publishing, 2022)
People increasingly understand that education at an early childhood is very impactful on the development of basic education. Children's basic education starts from early childhood education. One of the children’s developments is motor development. It is a broad opportunity to move, learning experiences to find, sensory motor activities which include the use of large and small muscles that allow children to have motor perceptual development. Therefore, the team carried out community service activities in Dalisodo Village to improve children's motor skills using the simple game method on August 25, 2022. Its aim is that mothers have knowledge in choosing the right games that can help children improve motor skills and can help children Dalisodo village growing to their full potential. This community service is carried out using by giving lectures and trainings for young mothers and toddlers in Dalisodo Village. The enthusiasm of the participants showed their curiosity in terms of games that could train children’s basic motor skills.